Design and Development of Android-Based Augmented Reality Educational Media on Computer Materials and Their Components at SMA Negeri 1 Rambatan - Setiawan, Fadley; Dewi, Ika Parma (Darul Yasin Al Sys, 2026)
Digital technology has become increasingly important in Informatics learning; however, the development of Android-based Augmented Reality media for computer component materials remains limited. This study aims to design and develop Android-based Augmented Reality educational media for learning computer materials and components at SMA Negeri 1 Rambatan. A research and development approach was employed using the Multimedia Development Life Cycle model, comprising the stages of concept, design, material collecting, assembly, testing, and distribution. The study involved 60 students selected through purposive sampling, two media experts, and two material experts. Data were collected through observation, documentation, expert validation questionnaires, and User Acceptance Testing, then analyzed using descriptive quantitative analysis and Aiken’s V. The findings indicate that the ARCompt application successfully presents 14 three-dimensional computer component models grouped into input devices, output devices, storage devices, and processing units. The User Acceptance Testing result obtained a mean score of 3.10, categorized as very good. Media expert validation produced an Aiken’s V score of 0.85, categorized as very valid, while material expert validation produced a score of 0.73, categorized as fairly valid. The study concludes that ARCompt is feasible as an interactive learning medium to support Informatics learning on computer components. These findings contribute to the development of technology-enhanced educational media and provide practical implications for integrating Android-based Augmented Reality into Informatics learning. Further research is recommended to examine the effectiveness of ARCompt through experimental research.